Human muscle glycogen metabolism during exercise. Effect of carbohydrate supplementation - Tsintzas, K.; Williams, C. (Sports Medicine, 1998)
Carbohydrate (CHO) ingestion during exercise, in the form of CHO-electrolyte beverages, leads to performance benefits during prolonged submaximal and variable intensity exercise. However, the mechanism underlying this ergogenic effect is less clear. Euglycaemia and oxidation of blood glucose at high rates late in exercise and a decreased rate of muscle glycogen utilisation (i.e. glycogen 'sparing') have been proposed as possible mechanisms underlying the ergogenic effect of CHO ingestion. The prevalence of one or the other mechanism depends on factors such as the type and intensity of exercise, amount, type and timing of CHO ingestion, and pre-exercise nutritional and training status of study participants. The type and intensity of exercise and the effect of these on blood glucose, plasma insulin and catecholamine levels, may play a major role in determining the rate of muscle glycogen utilisation when CHO is ingested during exercise. The ingestion of CHO (except fructose) at a rate of > 45 g/h, accompanied by a significant increase in plasma insulin levels, could lead to decreased muscle glycogen utilisation (particularly in type I fibres) during exercise. Endurance training and alterations in pre-exercise muscle glycogen levels do not seem to affect exogenous glucose oxidation during submaximal exercise. Thus, at least during low intensity or intermittent exercise, CHO ingestion could result in reduced muscle glycogen utilisation in well trained individuals with high resting muscle glycogen levels. Further research needs to concentrate on factors that regulate glucose uptake and energy metabolism in different types of muscle fibres during exercise with and without CHO ingestion.